Development of High‐Efficiency Molecular Adsorbent Recirculating System: Preliminary Report. Issue 10 (7th January 2014) - Marangoni, Roberto; Bellati, Giorgio; Castelli, Alessandro; Romagnoli, Elisabetta
<x xml:space="preserve">Abstract</x> Molecular Adsorbent Recirculating System (MARS) is a liver support system widely employed in the treatment of liver failure. The method is normally well tolerated. To develop a liver support system combining high efficiency and tolerability, we modified the MARS albumin circuit with the insertion of double adsorption units in parallel. Four patients have been treated with this modified method (high‐efficiency MARS, HE MARS): two had very high serum bilirubin and two had very high total bile acids. After a single MARS session bilirubin was reduced more with HE MARS than standard MARS (from 27.6 to 52.3% in patient A and from 27.9 to 49.1% in patient B), and bile acid reduction increased from 40 to 59.8% in patient C and from 39.9 to 60% in patient D. The results of this preliminary investigation in only a very small number of patients do support the possibility of developing a liver support system that combines good tolerability and high efficacy.